Perancangan Sistem Proses Validasi Pengiriman Unit Mobil Berbasis Website - Ebeneizer, Daniel; Harya Bima Dirgantara (UNIVERSITAS KALBIS, 2025)
Abstract: In the rapidly growing digital era, efficiency and accessibility of information have become crucial aspects in various sectors, including business, government, start-ups, education, and automotive. Along with the increasing scale of the company, the amount of data managed is also getting bigger, so a system that can simplify work and increase the productivity of each division is needed. Dashboard comes as an effective and adaptive data visualization solution to the needs of each user, both in the form of graphs, tables, and other indicators. By integrating dashboards in the company’s workflow, previously manual processes such as cross-divisional decision-making or approval can be done digitally, faster, and more efficiently, saving time and budget. This is especially relevant in the automotive industry, which demands high coordination in the process of shipping units from factories to end consumers. Based on the researcher’s experience in the Kemendikbudristek internship program and independent internship, it is found that the dashboard system has a vital role in the smooth operation of the company. Previous research also supports that implementing a good dashboard not only improves visual performance but also the efficiency of the database system used. Keywords: Dashboard, digitalization, automotive, work efficiency, data visualization, information system.